2016
DOI: 10.1186/s12905-015-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review on determinants of unmet need for family planning among women of reproductive age in low and middle income countries

Abstract: BackgroundPoor access and low contraceptive prevalence are common to many Low- and Middle-Income Countries (LMICs). Unmet need for family planning (FP), defined as the proportion of women wishing to limit or postpone child birth, but not using contraception, has been central to reproductive health efforts for decades and still remains relevant for most policy makers and FP programs in LMICs. There is still a lag in contraceptive uptake across regions resulting in high unmet need due to various socioeconomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
240
5
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(294 citation statements)
references
References 49 publications
(129 reference statements)
42
240
5
7
Order By: Relevance
“…The finding that the level of education of the respondent was positively correlated with contraceptive use in the last three months supports existing evidence which indicates direct relationship between education level and use of family planning methods [17,26]. Also the results provide a clear picture of the settings where the study was conducted, that is, urban settings with two-thirds of the participants having secondary level of education.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The finding that the level of education of the respondent was positively correlated with contraceptive use in the last three months supports existing evidence which indicates direct relationship between education level and use of family planning methods [17,26]. Also the results provide a clear picture of the settings where the study was conducted, that is, urban settings with two-thirds of the participants having secondary level of education.…”
Section: Discussionsupporting
confidence: 74%
“…The association demonstrated in this study between contraceptive use and parity is also reported elsewhere [17,18,27]. This finding may not be a new finding in the family planning domain but may have different implications in the conflict afflicted settings.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…No entanto, pode-se pensar que os serviços de saúde ainda não conseguem cumprir com esse papel de transformação, visto que a oferta de ações em saúde em planejamento familiar, principalmente no âmbito da atenção básica, se dá prioritariamente às mulheres. Isto pode estar a serviço de reforçar a ideia de que a responsabilidade de planejar a família é exclusiva das mulheres, uma vez que exclui de antemão os homens destas iniciativas (Ferreira et al, 2014;Wulifan, Brenner, Jahn, & De Allegri, 2016).…”
Section: [] Mas Acho Que Tem Que Vir Dos Dois (R O P 1)unclassified
“…Ademais, entende-se que o direcionamento das ações de planejamento familiar tanto para mulheres quanto para homens e casais, através de informação, educação e comunicação, pode ser uma abordagem mais eficaz para superar as necessidades não satisfeitas em planejamento familiar, as quais ainda são presentes nos países com população que apresenta renda baixa e média (Wulifan et al, 2016).…”
Section: [] Mas Acho Que Tem Que Vir Dos Dois (R O P 1)unclassified